Sześcioetapowa metoda nauczania informatyki w szkole podstawowej - Celiński, Maciej (Tomorrow's school? Tradition and (r)evolutions in education, 2023)
In this article, I focus on presenting the theoretical assumptions of the 6-step teaching method for the subject of computer science. The use of this teaching method by primary school teachers can significantly increase the quality of the content presented. The method indicated in this article was previously developed by the author of the thesis entitled The teaching and controlling program „Modern programmable logic circuits in the design of digital circuits with a large scale of integration”. The developed method was implemented in the ICON program for learning the basics of designing digital circuits in the base of modern programmable microcircuits. However, its universality allows the implementation of other content, tasks and items.